2018
DOI: 10.1371/journal.pone.0200577
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and obesity among 12-year-old Malaysian adolescents

Abstract: The epidemic of obesity in developed countries is commonly associated with poor dietary habit and sedentary lifestyle. However, other determinants, including education background and family income, may contribute towards the problem especially in developing countries. This study aimed to determine the influence of socioeconomic status (SES) on obesity among 12-year-old school adolescents in Terengganu, Malaysia. Body weight and height were measured and BMI was categorised based on WHO z-score cut-off points. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
9
33
3
3
Order By: Relevance
“…A study by Hui Tee, Gan, Tan, & Chin (2018) indicated that in the household whereby the maternal and paternal are both working to sustain the household expenses would not be particularly concern with the supply of nutritious food. Furthermore, the study by Hui Tee et al (2018) also the education level of maternal does have a contributing effect on the quality of food consumptions however paternal are only concern with the family bonding and being main breadwinner of the family which is supported by a study by (Ahmad, Zulaily, Shahril & Abdullah, 2018). In the study by (Ahmad, Zulaily, Shahril & Abdullah, 2018) also indicated that higher household income and smaller household sizes has direct effect with the socio economic status of the household with the possession of higher purchasing power and food affordability.…”
Section: Urban Poor In Malaysiamentioning
confidence: 88%
See 1 more Smart Citation
“…A study by Hui Tee, Gan, Tan, & Chin (2018) indicated that in the household whereby the maternal and paternal are both working to sustain the household expenses would not be particularly concern with the supply of nutritious food. Furthermore, the study by Hui Tee et al (2018) also the education level of maternal does have a contributing effect on the quality of food consumptions however paternal are only concern with the family bonding and being main breadwinner of the family which is supported by a study by (Ahmad, Zulaily, Shahril & Abdullah, 2018). In the study by (Ahmad, Zulaily, Shahril & Abdullah, 2018) also indicated that higher household income and smaller household sizes has direct effect with the socio economic status of the household with the possession of higher purchasing power and food affordability.…”
Section: Urban Poor In Malaysiamentioning
confidence: 88%
“…With rapid economic growth and new technology have brought significant impact towards the accessibility towards healthy and nutritious food. A study by Himmelgreen, Romero Daza, Vega, Brenes Cambronero, & Amador (2006) indicated that despite the increase in household income, food availability and health service, the rate of lifestyle related diseases such as coronary heart disease, hypertension, stroke and diabetes have been on the rise alongside with the rate of obesity to the economic growth of the respective developing countries (Ahmad, Zulaily, Shahril & Abdullah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto al nivel socioeconómico, se observa asociación sólo en los hombres, en quienes a mayor nivel socioeconómico mayor es el incremento del porcentaje de grasa corporal. Estos resultados coinciden con Ahmad A y colaboradores (2018), 35 sin embargo, el presente estudio no muestra asociación con respecto a las mujeres.…”
Section: Discussionunclassified
“…While childhood obesity is associated with high energy, high fat, and high sugar diets, many children are also unable to obtain the recommended intakes of fiber and other micronutrients, e.g., calcium and B vitamins, which are crucial for growth [ 9 ]. Nonetheless, sociodemographic factors, such as gender, household income, parents’ occupation and educational level, also contribute toward childhood obesity in Malaysia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%